Parasitosis intestinal de los niños de la escuela Mario Paltin Lavanda de la comunidad El Progreso Del Cantón Chinchipe. Año 2014 - Paqui Quizhpe, Carlos Eduardo (2016)
This research work was to determine Intestinal Parasites children School Mario paltin Lavender's Progress Chinchipe Canton community. The research design was cross-sectional, prospective, descriptive, and bibliographic field. technical survey and direct observation with instruments questionnaire and observation guide applied to 65 school children was used to obtain information; the results were: prevalence of parasitosis in children Mario School paltin Lavender 100%, the 50.77% are male, between the ages of 5-7 years in 36.92%, 100% are of mixed cultural group , and 86.15% of children live with their parents; the most common type of parasite in school are Ascaris lumbricoides with 38.46%; For the development of the intervention plan proceeded to carry out educational activities on hygiene measures and antiparasitic medical treatment for school children based on laboratory results because there misapplication of hygienic measures is related to the consumption of water, poor hygiene and power causing parasite infestation in the body. In conclusion, the study of intestinal parasitosis performed on school children Mario paltin Lavender determined that the prevalence of intestinal parasitosis is 100% and the parasite that causes a higher percentage of Ascaris lumbricoides. Keywords: Intestinal parasites, children, school, community